Dance in writing: communication in writings about dance (Urdimento: Revista de Estudos em Artes Cênicas, 2020)
Written approaches to western performing dance are here considered in a proposal for a division into four groups: manuals, theory, history, and criticism. A key concern in dealing with them is the idea that dance is a language: a kind of communication organized in its own system, that is elaborated and explored in a particular way by each kind of writing. This investigation addresses questions such as why we would write about dance, and what we would write about dance, by discussing the specificity of dance writings, their relevance, and forms of presenting and developing fundamental elements of dance communication.
Keywords: Dance; Communication; Text dance texts; Writing